Development of “small schools” in rural areas - Sommer-Sutter, Bigna (Swiss Journal of Educational Research, 2012)
This article deals with the development of small schools in rural alpine areas in three different linguistic regions. On the basis of case studies, a number of small schools’ different local inventive solutions will be discussed. The question of which influencing variables drive innovative developments will also be analysed. Additionally, this article aims to identify factors of success for the sustainable implementation of innovations to preserve small schools in peripheral regions.